Clickers, iPad, and Lecture Capture in One Semester: My Teaching Transformation. Issue 6 (2nd July 2016) - Latulippe, Joe
Abstract: Using technology to enhance the classroom environment can have a tremendous impact on student learning, as well as on an instructor's teaching. This paper describes one instructor's transition from traditional chalkboard lectures to a fully technological presentation of content. After carefully reviewing the literature, clicker technology was introduced to increase student participation and use peer instruction activities through voting. To maximize the effectiveness of clickers, using a tablet in teaching and explorations with lecture capture were natural next steps in increased use of technology. Presented here are the author's reflections on the transformation process as well as insight into how the technology allows for more active student engagement in class.